A28 RELATIVE RATES OF ULCERATIVE COLITIS TO CROHN'S DISEASE: PARALLEL EPIDEMIOLOGIES IN NEWLY VS. HIGHLY INDUSTRIALIZED COUNTRIES. (26th February 2020) - Windsor, J W; Buie, M; Coward, S; Gearry, R; Hansen, T; King, J A; Kotze, P; Ma, C; Ng, S; Panaccione, N; Panaccione, R; Quan, J; et al.
Abstract: Background: Inflammatory bowel disease (IBD) first presents in a population as cases of ulcerative colitis (UC) followed by cases of Crohn's disease (CD). Newly industrialized countries (NIC) show a prallel epidemiology of IBD to highly industrialized countries (HIC) in the previous century; one marker of this is the relative incidence/prevalence rates of UC to CD, which approximates 1 over time. Aims: Provide evidence for the UC:CD ratio as a proxy for disease penatrance in a population. Methods: Systematic review of MedLine and Embase for studies reporting incidence or prevalence of UC and CD. Log-linear regression (by region and NIC/HIC [2019 United Nations definitions]) was used to calculate average annual percent change (AAPC) and associated 95% confidence intervals (CI). Data were plotted on an online, interactive map to show trends (link provided). Results: We extracted data from 218 studies compising population-level data from 69 countries. We found negative AAPCs as the prevalence ratio of UC:CD significantly decreased over time in East Asia, West Asia, North Europe, and South Europe; 6/12 global regions displayed significantly decreasing incidence ratios. No AAPC was found to be significantly increasing (Table 1). When examing HIC/NIC, we found a significant effect of NIC on the UC:CD prevalence ratio after 2000 (AAPC:−3.83;95%CI:−6.28, −1.31) while HIC regions remained stable (AAPC:2.14;95%CI:−1.40, 5.82). Looking at all available data, both HICs and NICs show significantly decreasing UC:CD prevalence ratios (HIC:AAPC:−3.72;95% CI:−4.46, −2.97; NIC:AAPC:−2.62;95%CI:−4.13, −1.08). Conclusions: In some HICs (eg. Canada), the UC:CD incidence ratio was <1 in the earliest available data (1966), explaining the stable AAPC in North America (AAPC:−0.24;95%CI:−1.12, 0.65). However, in NICs (eg. Southern Asia), the AAPC is rapidly decreasing (AAPC:−24.68;95%CI:−37.85, −8.71) as areas like Sri Lanka rapidly fall from an incidence ratio of 7.5 (2007) to 2.8 (2012), mimicking trends in IBD epidimeology of HICs in the previous century. Funding Agencies: None